New refinements of the Jensen-Mercer inequality associated to positive $n$-tuples - Adil Khan, Muhammad; Pečarić, Josip (Armenian Journal of Mathematics, 2022)
In this manuscript, we propose new refinements for the Jensen-Mercer as well as variant of the Jensen-Mercer inequalities associated to certain positive tuples. We give some related integral version and present applications for different means. At the end, further generalizations are given which are associated to $m$ finite sequences.